General Practitioners Assessment Highlights Excellent Patient Satisfaction Following Bar Removal after Nuss Procedure in Children and Adolescents - Hennig, Mandy; Kuebler, Joachim F.; Petersen, Claus; Metzelder, Martin L. (European Journal of Pediatric Surgery, 2012)
Background We recently demonstrated that minimally invasive repair of pectus excavatum (MIRPE) achieves a lasting patient satisfaction after bar removal. This correlated with parent ratings. It has been postulated that patient ratings may be biased by high preoperative patient expectations. The aim of this study was to compare patient self-assessment with general practitioners (GPs) assessment.Methods Of the 39 patients who underwent bar removal after MIRPE between 2002 and 2006, 39 GPs were asked to answer a modified version of a former single-step questionnaire to evaluate their opinion on psychosocial and physical well-being of their patients. The subjective patient ratings were compared with the GP ratings.Results Of the 39 GPs, 22 (56%) completed a questionnaire and assessed the outcome of the Nuss procedure. There was a highly significant correlation between GP and patient ratings (p < 0.001; correlation coefficient = 0.437). Mean total scores obtained from GPs were similar to patient scores (63.4 ± 2.6 SEM vs. 67.5 ± 2.4 SEM; not significant [NS]). Detailed analysis revealed that GPs scored several items differently to their patients: GPs scored social activity (p < 0.05) and preoperative self-esteem (p < 0.05) significantly lower, but pain episodes (p < 0.05) and impairment of daily activities (p < 0.05) during the period with the implanted bar significantly higher than their patients. Comparison of the 17 nonassessed cases, with the self-assessment of 22 patients with GP assessment, revealed no significant difference, making an analytical bias unlikely (67.5 ± 2.4 SEM vs. 67.3 ± 2.8 SEM; NS).Conclusion GPs found a higher impairment of patient well-being during the period with an implanted bar, which might be related to the high patient motivation to cope with bar impairment. However, the all over GP and patient satisfaction was similar and excellent.
Keywords: pectus excavatum; Nuss procedure; single-step questionnaire; assessment of satisfaction; general practitioner